1999
DOI: 10.1080/002075499190770
|View full text |Cite
|
Sign up to set email alerts
|

Reacting JIT ordering systems to the unstable changes in demand

Abstract: In order to realize an agile control for multi-stage production inventory systems, this paper proposes reactive JIT (Just-in-Time) ordering systems for the unstable changes in demand. Two JIT ordering systems, the Kanban system and the concurrent ordering system, are dealt with. For the JIT ordering systems, a reactive controller of bu er size is proposed in this paper. In the proposed systems, the unstable changes in demand are detected with the exponentially weighted moving average charts, and the bu er size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…Stochastic learning automata methods [2] were used to model the learning behavior of the system. Using a statistical control chart, Takahashi and Nakamura [14] proposed a reactive Kanban system that can detect unstable changes in demand timely. The number of Kanbans as a reaction to detect unstable situation is a control parameter.…”
Section: Literature Surveymentioning
confidence: 99%
“…Stochastic learning automata methods [2] were used to model the learning behavior of the system. Using a statistical control chart, Takahashi and Nakamura [14] proposed a reactive Kanban system that can detect unstable changes in demand timely. The number of Kanbans as a reaction to detect unstable situation is a control parameter.…”
Section: Literature Surveymentioning
confidence: 99%
“…They demonstrated that in such environments, FKS outperforms the traditional kanban system. Other adaptive and reactive techniques to adjust the number of kanbans were proposed by Tardif and Maaseidvaag [23], Takahashi and Nakamura [24,25,26] and Takahashi et al [27]. Kizilkaya and Gupta [28], Udomsawat and Gupta [29,30], Nakashima, Kojima and Gupta [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, in order to minimize twip while maintaining wt at less than a certain level, the allocation of work elements and/or the buffer size should be altered in response to the changed r. In responding to the changed r, altering only the buffer size is insufficient, but the allocation of work elements should be also altered. For example, in order to minimize twip while maintaining w/<0.20, the buffer size should be altered from (2,5) to (2,6) in response to changes in r from [0,1.4) to [1.4, 0.2] under allocation 1. In order to respond to changes in r as r>0.2, it is difficult to maintain >v/<0.2 even if the buffer size is altered.…”
Section: Results and Implicationsmentioning
confidence: 99%
“…Various control charts have been developed, and the EWMA chart [5] is utilized to detect small changes quickly. In this paper, the EWMA chart is utilized to detect unstable changes in demand like Takahashi and Nakamura [2]. At first, the monitored time series data dij are filtered by exponential smoothing, a kind of lowpass filter, and the EWMA ///y are calculated as follows;…”
Section: Detecting Unstable Changesmentioning
confidence: 99%
See 1 more Smart Citation